ANALISIS ASPEK EKONOMI POLITIK PROSES AGENDA SETTING DALAM KEBIJAKAN KERJASAMA PEMBANGUNAN PASAR DI KOTA SALATIGA - Lelana, Hayuning Putri; -, Warsito -; Harsasto, Priyatno - (Journal of Politic and Government Studies, 2018)
The burning case of Rejosari Market in 2008 resulted in the Salatiga City Government taking political steps to hold a third party in the development of Pasar Rejosari. The complexity of cooperation with Salatiga municipal government and investors in the market development in Salatiga city because it tends to cause a burdensome impact on the traders and the development of the market that has not been able to build maximum has attracted researchers to examine the political economy aspects related to the cooperation through the government's policy-making process. The theory used in the research is public policy theory which focuses on the interaction of actors in the policy process so that the theoretical reference in this research through the flow of policy agenda agenda is problems streams, policy streams, and political streams resulting in policy window in government policy making. The method used with the type of qualitative research through descriptive analysis approach. In this study found that there are influential actors who bring one investor in the policy of cooperation resulting in a split between traders Rejosari Market and the formation of new market community. Development that does not occur due to administrative problems makes the atmosphere becomes unfavorable and exploited by other political elite actors for the existence of a particular political party.Keywords: cooperation, public policy, agenda setting